Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2}$$

I can solve it using l'Hôpital but just cannot find a way to do it algebraically.

share|cite|improve this question
What limit are you trying to find? – Chris Eagle Feb 18 '13 at 21:19
Limit as $x$ goes to what? – Jim Feb 18 '13 at 21:19
@user62872 No limit, no question. It's an easy downvote. But I'll refrain from doing that to give you time to properly ask the question. – Git Gud Feb 18 '13 at 21:20
I am sorry limit as x approaches 0, couldnt find how to edit the original post – user62872 Feb 18 '13 at 21:20
@user62872 No problem. Don't forget to upvote answers which you find helpful and accept your favorite one. – Git Gud Feb 18 '13 at 21:24

4 Answers 4

up vote 3 down vote accepted

Multiply the top and bottom by $2\sqrt{x + 1} + x + 2$.

share|cite|improve this answer

$$\begin{align} \lim_{x\to 0}\frac{2\sqrt{x+1}-x-2}{x^2} &= \lim_{x\to 0}\frac{2\sqrt{x+1}-(x+2)}{x^2} \frac{2\sqrt{x+1}+(x+2)}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{4(x+1)-(x+2)^2}{x^2} \frac{1}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{4(x+1)-(x^2+4x+4)}{x^2} \frac{1}{2\sqrt{x+1}+x+2}\\ &= \lim_{x\to 0}\frac{-x^2}{x^2}\frac{1}{2\sqrt{x+1}+x+2}\\ &=\lim_{x\to 0}\frac{-1}{2\sqrt{x+1}+x+2}\\ &=-\frac{1}{4} \end{align}$$

share|cite|improve this answer
There's a typo in the last $\lim$. Nice answer. – Git Gud Feb 18 '13 at 21:35
I believe you left out a negative somewhere, nice work though – user62872 Feb 18 '13 at 21:36

$$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2} = \lim_{x\to 0} \dfrac{2\sqrt{x+1} - (x + 2)}{x^2}$$

To start, multiply numerator and denominator by the conjugate $$2\sqrt{x + 1} + (x + 2)$$

share|cite|improve this answer
Thank you, I had a dumb parentheses mistake – user62872 Feb 18 '13 at 21:37
You're welcome, user62872! – amWhy Feb 18 '13 at 21:53

We have $\sqrt{1+x}=1+\frac{1}{2}x+(\frac{1}{2})(\frac{-1}{2})\frac{x^2}{2}+o(x^2)$, so $$\lim_{x \to 0} \dfrac{2\sqrt{x+1}-x-2}{x^2}=\lim_{x \to 0}\dfrac{-\frac{1}{4}x^2+o(x^2)}{x^2}=-\frac{1}{4}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.